(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A lawn mower is a cleaning tool commonly used to cut grasses. Some lawn mowers have been used in the industry, including the push mower, ride-on mower, rotary mower, and self- propelled mowers. This project research aims to develop an innovative lawn mower machine that performs tasks and helps reduce the cost of help for cutting grass in their lawn area. This machine is a more environmentally friendly alternative to gas-powered products. The overall testing accuracy of this hand gestures-controlled lawn mower cleaning machine was evaluated with 100%, and given the overall mean score of 3.57, it was interpreted as strongly agreeable. These results indicate that all of the respondents, which are the gardeners and homeowners of Vista Verde North Executive Village, shared a common high score evaluation. Therefore, the research shows that the components used, including the Arduino Nano as a microcontroller and the MPU6050 Gyroscope sensor, are effective materials in building the product.